RELATION BETWEEN THE CREATIVE ATTITUDES AND THE PERFECTIONISM OF THE HIGH SCHOOL STUDENTS (Annual of the Faculty of Philosophy in Skopje, 2009)
This study presents the findings gathered with the research, which aim was to determine if there was any relation between the person's creative attitudes and the positive and negative perfectionism, and afterwards to check if there were differences between the positive and the negative perfectionists concerning the creative attitudes. For better validity of the study, the difference between the extremely positive and the extremely negative perfectionists concerning the creative attitudes was also examined.This research was conducted on an adequate sample of 82 third year students from one High school in Skopje, who were tested with the Positive And Negative Perfectionism Scale (PANPS) and the Test for Creative Attitudes (TCA).In processing the results, the following statistics procedures have been used: arithmetic mean (M), standard deviations (SD), Pearson coefficient of correlation (r), F-test for checking the homogeneity between variances and t-test for checking the differences between arithmetical means. According to the obtained data, it can be concluded that: the creative attitudes are positively related to the positive perfectionism, and negatively with the negative perfectionism; the increase of the positive perfectionism is followed by the increase of the creative attitudes; the increased negative perfectionism is followed by decreased creative attitudes.
Keywords: CREATIVE ATTITUDES; PERFECTIONISM; POSITIVE PERFECTIONISM; NEGATIVE PERFECTIONISM